Implication of osteoplastic flap for frontal sinus surgery in the endoscopic era - Devaraj, Aishwarya Raj Pillai; Prasad, Kothegala Chandrashekariah; Karunasagar, Abhilasha; Pappanacherry, Manna Jose; Gowda, Harshitha Naganna; Nair, Sreelekshmi Sukumaran; Subramani, Brindha Hennur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
In the present era where functional endoscopic sinus surgery is the mainstay of management for any frontal sinus disease, we present a case series comprising six cases of various frontal sinus pathology that were managed with an external approach using a bicoronal osteoplastic flap technique of which three cases were of inverted papilloma, one case of allergic fungal rhinosinusitis, one case of frontal mucocele and a case of road traffic accident with frontal bone and nasal bone fracture. The cases had a mean follow-up period of 6 months. There was no recurrence of disease and no significant postoperative complications have been reported during the follow-up period so far. Osteoplastic anterior wall approach to the frontal sinus has proved to be one of the most effective, simple, and reliable procedures with excellent success rate and good cosmesis.